2022
DOI: 10.1111/myc.13487
|View full text |Cite
|
Sign up to set email alerts
|

Could cattle dung burning have contributed to the epidemic of COVID‐19‐associated mucormycosis in India? Results of an experimental aero‐mycological study

Abstract: Background Several hypotheses have been proposed for explaining the outbreak of coronavirus disease 2019 (COVID‐19)‐associated mucormycosis in India, including the burning of cattle dung cakes, though no study has yet been conducted to support this claim. Methods We conducted an aero‐mycological study to evaluate whether Mucorales in the air increased during or after burning cattle dung cakes. We further compared the growth of Mucorales in the indoor air samples from ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Nonetheless, we provide weak indirect evidence implicating the severity of COVID-19 illness (elevated C-reactive protein) in the development of CAM. Finally, rural residence was significantly associated with CAM and might be attributed to higher levels of fungal spores in the rural environment (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Nonetheless, we provide weak indirect evidence implicating the severity of COVID-19 illness (elevated C-reactive protein) in the development of CAM. Finally, rural residence was significantly associated with CAM and might be attributed to higher levels of fungal spores in the rural environment (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 98%
“…Based on a few media reports, 1 review hypothesized that the burning of cow dung led to the mucormycosis outbreak in India (27). However, a recent experimental aeromycological study found no evidence for this theory (25). Several case-control studies (n = 13) have assessed the risk factors associated with CAM (Appendix Table 8) (6,7,20,21,(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, we observed a significantly smaller proportion of community controls (3%) on insulin therapy than those at the hospital (39%; 17 Further, a recent aero-mycological study found no association between the burning of cattle dung cake and Mucoralean spore burden in the ambient air. 18 The aero-mycological study, however, did not include any patient data. The current study disproved the cattle dung hypothesis and identified poor control of diabetes (higher glycated haemoglobin) and other factors associated with PM in DM.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…The use of cow-dung to treat COVID-19 or the burning of cow-dung cakes causing spore dispersal and increased risk of CAM was postulated as a risk. However, there was no change in growth of Mucorales in air samples collected before and after cattle dung burning in an aero-mycological study done in India during the COVID-19 period [ 78 ].…”
Section: Environmental Epidemiologymentioning
confidence: 99%